Optimization of a Gas Switching Combustion process through advanced heat management strategies. (1st January 2017) - Cloete, Schalk; Zaabout, Abdelghafour; Romano, Matteo C.; Chiesa, Paolo; Lozza, Giovanni; Gallucci, Fausto; van Sint Annaland, Martin; Amini, Shahriar
Highlights: GSC is a promising new reactor concept for power production with cost effective CO2 capture. The standalone fluidized bed reactors employed will allow for easy process scale-up. The GSC simple configuration achieves higher efficiencies than conventional solutions. Further increases in efficiency can be achieved via advanced heat management. The 41.9% maximum efficiency is in line with other CLC–IGCC configurations. Abstract: Gas Switching Combustion (GSC) is a promising new process concept for energy efficient power production with integrated CO2 capture. In comparison to conventional Chemical Looping Combustion (CLC) carried out in interconnected fluidized beds, the GSC concept will be substantially easier to design and scale up, especially for pressurized conditions. One potential drawback of the GSC concept is the gradual temperature variation over the transient process cycle, which leads to a drop in electric efficiency of the plant. This article investigates heat management strategies to mitigate this issue both through simulations and experiments. Simulation studies of the GSC concept integrated into an IGCC power plant show that heat management using a nitrogen recycle stream can increase plant efficiency by 3 percentage points to 41.6% while maintaining CO2 capture ratios close to 90%. Reactive multiphase flow simulations of the GSC reactor also showed that heat management can eliminate fuel slip problems. In addition, the GSC concept offers the potential to remove the need for a nitrogen recycle stream by implementing a concentrated air injection that extracts heat while only a small percentage of oxygen reacts. Experiments have shown that, similar to nitrogen recycle, this strategy reduces transient temperature variations across the cycle and therefore merits further investigation.